1996
DOI: 10.1161/01.res.79.5.1031
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelium-Related Mechanisms in the Pathophysiology of Renal Ischemia/Reperfusion in Normal Rabbits

Abstract: The present study addressed the effect of interventions aimed to increase NO in the setting of acute renal ischemia/reperfusion (I/R) in uninephrectomized rabbits. In the 60-minute post-I/R period, L-arginine+superoxide (O2.-) dismutase (SOD) synergistically improved the renal functional (69.4% versus 10.4% of the pre-I/R glomerular filtration rate with or without L-arginine+SOD, respectively; p < .01) and histological parameters (82.9% decrease of medullary congestion in L-arginine+SOD, P < .01 versus vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 36 publications
5
37
0
1
Order By: Relevance
“…The kidneys were preserved in phosphate-buffered 10% formalin (pH 7.4), after which the kidneys were chopped into small pieces, embedded in paraffin wax, cut at 4 mm, and stained with hematoxylin and eosin. Histopathological changes were analyzed for tubular necrosis and proteinaceous casts as described by Caramelo et al (16). These lesions were graded as follows: no damage (0), mild (1: unicellular, patchy isolated damage), moderate (2: damage less than 25%), severe (3: damage between 25% and 50%), and very severe (4: more than 50% damage).…”
Section: Histological Studiesmentioning
confidence: 99%
“…The kidneys were preserved in phosphate-buffered 10% formalin (pH 7.4), after which the kidneys were chopped into small pieces, embedded in paraffin wax, cut at 4 mm, and stained with hematoxylin and eosin. Histopathological changes were analyzed for tubular necrosis and proteinaceous casts as described by Caramelo et al (16). These lesions were graded as follows: no damage (0), mild (1: unicellular, patchy isolated damage), moderate (2: damage less than 25%), severe (3: damage between 25% and 50%), and very severe (4: more than 50% damage).…”
Section: Histological Studiesmentioning
confidence: 99%
“…The kidneys were then fixed in phosphate-buffered 10% formalin, pH 7.4, after which they were chopped into small pieces, embedded in paraffin wax, cut at 4 m, and stained with hematoxylin and eosin. Histopathological changes were analyzed for tubular necrosis, proteinaceous cast, and medullary congestion, as described by Caramelo et al (1996). Tubular necrosis and proteinaceous casts were graded as follows: no damage (severity score 0), mild (1, unicellular, patchy isolated damage), moderate (2, damage less than 25%), severe (3, damage between 25 and 50%), and very severe (4, more than 50% damage).…”
Section: Methodsmentioning
confidence: 99%
“…Caramelo et al (14) administered superoxide dismutase together with L-arginine and demonstrated that there is a remarkable increase in renal functions and urine volume and that this arises from the synergistic effects of these two substances. Burra et al (15) expressed that L-arginine therapy reduces histopathological injury in pigs that have been exposed to renal I/R.…”
Section: Lahera Et Al (4) Performed Hemodynamic Examinations To Keepmentioning
confidence: 99%